Homozygosity for Pericentric Inversions of Chromosome 9 in a Patient's Parents with Stillbirth- Report of a New Case and Review of Literature - M Khaleghian; C Azimi (Tehran University of Medical Sciences, 2006)
Pericentric inversions of chromosome 9 are among the most frequent chromosomal rearrangement in human. A few cytogeneticists consider inversions of chromosome 9 as a normal variant. However, many reports in the recent literature link pericentric inversions of chromosome 9 with infertility, recurrent abortions, and a number of other abnormal conditions. We report a case of homozygosity pericentric inversions of chromosome 9 in a woman with 28- wk stillbirth. In this case, her both parents were heterozygotes for the inversions of chromosome 9.